Barriers and norms regarding kidney transplantation on the Pine Ridge Indian Reservation - Reedy, Julia E., author (Colorado State University. Libraries, 2017)
American Indian populations in the United States have, in recent years, been plagued by a diabetes epidemic of catastrophic proportions. On the Pine Ridge Indian Reservation, located in southwest South Dakota, discrimination, extreme poverty, rampant unemployment, limited access to healthy foods, and other factors have led the Oglala Lakota population to have the highest rates of End-stage renal disease (ESRD). Despite high rates of ESRD, American Indian populations have the lowest rates of kidney transplantation. This research explores the political economic barriers and cultural norms surrounding kidney transplantation as a treatment option for ESRD on the Pine Ridge Reservation.
Barriers and norms regarding kidney transplantation on Pine Ridge Reservation
241 - Julia Elaine Reedy
Keywords: Pine Ridge Indian Reservation; kidney transplantation; Lakota; end-stage renal disease; political economy